Fate of Bacillus anthracis during production of laboratory-scale cream cheese and homemade-style yoghurt. (April 2015) - Mertens, Katja; Schneider, Oda; Schmoock, Gernot; Melzer, Falk; Elschner, Mandy C.
Abstract: The viability of Bacillus anthracis during production and storage of cream cheese and yoghurt was evaluated. Experimental cheeses were manufactured from whole milk inoculated with a suspension of B. anthracis vegetative cells and spores at a final concentration of 10 4 cfu/ml. Lactic acid bacteria (LAB) and lab ferment were used to induce milk ripening and milk coagulation. The pH-value of the contaminated milk dropped below 4.5 within the first 6 h and the amount of LAB increased by approximately 2-logs. During cheese production and storage at 5–9 °C for 24 days no growth of B. anthracis was observed. The amount of vegetative cells and spores fluctuated by 1-log. Inoculation of whole milk with heat-treated spores at 10 4 cfu/ml resulted in a slight increase of vegetative cell counts during the first 6 h. This indicated that germination occurred, but replication of vegetative cells was still inhibited in the produced cheese. Incubation of cheeses at room temperature or heating after milk coagulation strongly reduced the amount of LAB but had no effect on the growth behaviour of B. anthracis . The vegetative cell and spore content remained steady at 10 4 cfu/100 mg. During yoghurt production the pH-value decreased within 5 h below 5 and growth of B. anthracis was inhibited throughout storage. A pH-value of 5 or less is likely a critical factor to control the growth of B. anthracis . However, spores remained viable in experimental cream cheeses and yoghurts and are a potential risk of infection. Highlights: Bacillus anthracis remains viable during cream cheese and yoghurt production. Germination can occur during the first hours of fermentation. Decrease of the pH < 5 is critical for growth inhibition of B. anthracis.